MICROSCOPIC AND SPECTROSCOPIC INVESTIGATION OF THE CALCITE SURFACE INTERACTED WITH HG(II) IN AQUEOUS SOLUTIONS - Godelitsas A.; Astilleros J.M.; Löns J.; Putnis A.; Hallam K.R. (My University, 2003)
The interaction of the {101¯4} cleavage surface of calcite with Hg(CH3COO)2 aqueous solutions with concentration of 5 mM Hg(II) (pH 3.5), was investigated using microscopic and spectroscopic techniques. In situ atomic force microscopy experiments showed that surface microtopography changes significantly as a result of the interaction, and that the initial rhombic etch pits induced by H2O dissolution are rapidly transformed to deeper etch pits exhibiting an unusual triangular shape. The growth of these etch pits is strongly anisotropic, moving faster along the [221] direction than along the [010] direction (with step-retreat velocities of ~12 nm s-1 and ~4 nm s-1, respectively). The modified etch pits are due to Hg(II) sorption in the surface, rather than due to the effect of the acetate anion. The sorption (adsorption and probably absorption also) of Hg(II), in the first minutes of the interaction, is shown by X-ray photoelectron spectroscopy. After ~2 h, the triangular etch pits are interconnected to form larger hexagonal etch pits, while Hg(II)-bearing phases (confirmed later by SEM-EDS) grow onto the surface through a heterogeneous nucleation process. The crystal growth of orthorhombic (montroydite-type) hydrated Hg(II) oxide (HgO·nH2O) on the surface of calcite was confirmed by XRD patterns and FT-IR spectra from samples exposed for longer times to Hg(CH3COO)2 solution.
Keywords: Calcite